Validation of diabetic ulcer severity score - Kummankandath, Sidhic Abbas; Mohammed, Suaib T; Karatparambil, Abid A; Nadakkavil, Mujeeb Rahman Mohammed; Pappala, Rahul Tej (International Surgery Journal, 2016)
Background:To assess the efficacy of Diabetic Ulcer Severity Score (DUSS), a wound-based clinical scoring system for diabetic foot ulcers in anticipating the clinical outcomes. Design: Prospective study. Methods: Total of 200 Diabetic patients with foot ulcers attending surgical outpatient clinic or admitted into the hospital, irrespective of duration of ulcer from February 2014 to November 2015 were included in the study. Necessary data was collected. DUSS score was calculated for each patient and analysis was done using SPSS package version 17. Results:Most commonly ulcers were of DUSS Score of 2 and 3. Overall 107 of 200 people had amputations in our study. Amputations were more common in patients with DUSS score 4 followed by 3. Major amputation was common in patients with DUSS score 4, none of the patients with score 0, 1 and 2 had major amputation, minor amputations were more common in patients with DUSS score of 3. The probability of healing without amputation with score 0 was 100% and decreases to 5.71% with score 4. Conclusions:DUSS scoring system provides an easy diagnostic tool for anticipating probability of healing /amputation and need for surgery by combining four clinically assessable wound based parameters. It can be very helpful for the stratification of study groups depending on severity of ulcers and it provides a simple, streamlined approach in a clinical setting that requires no investigative equipment although subsequent adequate Wound care is an indispensable prerequisite to the DUSS being a valid diagnostic tool.